(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The study was carried out to analyze the various phytochemical properties and to determine the in-vitro antimicrobial activity of Parkia biglobosa methanolic leaf extract against Methicillin-Resistant Staphylococcus aureus (MRSA). Materials and methods: The phytochemical screening and Thin Layer Chromatography (TLC) of the methanol extract were conducted using standard methods. The antimicrobial activity of the P. biglobosa methanolic leaf extract on sheep and human MRSA isolates was investigated by disc diffusion method. The extract was tested at different concentrations of 100, 200 and 400 mg/mL and norfloxacin (10 µg) as control. The MIC/MBC were determined by serial dilution method in broth media. Results: the phytochemical analysis showed the presence of alkaloid, saponins, tannins, cardiac glycosides, flavonoids and terpenoids while TLC result revealed 5 spots with retention factor (Rf) values of 0.14, 0.34, 0.42, 0.56 and 0.66 depicting different component using methanol and chloroform at the ratio of 4:1 as solvent system. The diameter of inhibition zone (DIZ) of the extract on MRSA isolates cultured on agar plate revealed a dose dependent response. The extract had the highest DIZ average replicate value of 20.66±1.76 against human MRSA isolates and 20.66±1.20 was recorded as highest DIZ on the sheep MRSA isolates. Norfloxacin had the highest DIZ of 20.33±0.57 on sheep MRSA isolates and 20.33±1.52 DIZ against human isolates. MIC/MBC revealed the highest values of 6.25 mg/mL/12.5 mg/mL for both sheep and human MRSA isolates. Conclusion: The susceptibility test of crude methanol extract of P. biglobosa leaf has revealed activity against MRSA. Thereby, attesting to the folkloric claim of using P. biglobosa for ethno-therapeutic purposes against infectious diseases in Nigeria and other places. http://doi.org/10.5455/javar.2018.e263